A single‐cell‐gap transflective blue‐phase liquid crystal display based on fringe in‐plane switching electrodes. Issue 9 (20th January 2020) - Zhou, Xiang‐Yu; Chu, Fan; Tian, Li‐Lan; Li, Rui; Hou, Wen‐Yi; Gu, Xiao‐Qing; Wang, Qiong‐Hua
Abstract: A transflective blue‐phase liquid crystal display (TRBP‐LCD) based on fringe in‐plane switching (FIS) electrodes is proposed. The proposed structure generates combined fringe and in‐plane electric fields that cause more liquid crystal (LC) molecules to reorient almost in plane above and between the pixel electrodes. The fringe field is mainly generated in the transmissive (T) region, and the horizontal electric field is mainly generated in the reflective (R) region. By optimizing the width of the pixel electrodes and the gap between two adjacent pixel electrodes, the different electric field intensity in the T and R regions contribute to balance the optical phase retardation between the T and R regions. As a result, the proposed TRBP‐LCD exhibits a low operating voltage and high optical efficiency, while it preserves a relatively simple fabrication process. Abstract : A transflective blue‐phase liquid crystal display (TRBP‐LCD) based on fringe in‐plane switching (FIS) electrodes is proposed.